Scale‐up of a Type I secretion system in E. coli using a defined mineral medium. (4th November 2019) - Ihling, Nina; Uhde, Andreas; Scholz, Romy; Schwarz, Christian; Schmitt, Lutz; Büchs, Jochen
Abstract: Secretion of heterologous proteins into the culture supernatant in laboratory strains of Escherichia coli is possible by utilizing a Type I secretion system (T1SS). One prominent example for a T1SS is based on the hemolysin A toxin. With this system, heterologous protein secretion has already been achieved. However, no cultivations in a defined mineral medium and in stirred tank bioreactors have been described in literature up to now, hampering the broad applicability of the system. In this study, a mineral medium was developed for cultivation under defined conditions. With this medium, the full potential and advantage of a secretion system in E. coli (low secretion of host proteins, no contamination with proteins from complex media compounds) can now be exploited. Additionally, quantification of the protein amount in the supernatant was demonstrated by application of the Bradford assay. In this work, host cell behavior was described in small scale by online monitoring of the oxygen transfer rate. Scalability was demonstrated by stirred tank fermentation yielding 540 mg/L HlyA1 in the supernatant. This work enhances the applicability of a protein secretion system in E. coli and paves the way for an industrial application.